Foundational Patient Experience: Analyzing 10 Years of Patient Experience Research - Geoffrey Silvera; Courtney Haun; Varun Natarajan (Patient Experience Journal)
In this study, we seek to provide a critical examination of the field of Patient Experience (PX) by using citation analysis to determine the foundational keystones of the PX knowledge base. This study will employ a systematic citation analysis to evaluate the articles published in the Patient Experience Journal (PXJ), focusing on citation frequency as evidence of impact on the field. To achieve this, we examine the entire corpus of article citations published in the PXJ from 2014–2023 (Volumes 1–10). By examining a corpus consisting of 515 independent articles (N=515) that include over 12,000 references (n=12,712) over the course of a decade, we aim to provide a scope of the foundational knowledge in PX. The result of this analysis finds the top 10 most cited articles across the first decade of PX scholarship, each having important implications for the future of patient experience.